1997
DOI: 10.1111/j.1348-0421.1997.tb01196.x
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic and Genetic Variations among Japanese Encephalitis Virus Strains Belonging to Genotype 1

Abstract: Hyperimmune antisera against four Japanese encephalitis (JE) virus strains, ThCMAr4492 and ThCMAr6793 from Thailand and Nakayama and JaGAr01 from Japan, were used to analyze the antigenic relationships among 12 Thai strains belonging to genotype 1, and two Japanese strains and one Chinese strain belonging to genotype 3. The antiserum for ThCMAr6793 significantly neutralized nine of the 12 Thai strains, none of which was significantly neutralized by antisera for the Nakayama and JaGAr01 strains. The antiserum f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 35 publications
(53 reference statements)
4
43
0
1
Order By: Relevance
“…It is estimated that JEV causes 35,000 to 50,000 cases of encephalitis, including 10,000 deaths and as many neurologic sequelae, each year (61). Although only one JEV serotype is known to exist, cross-neutralization experiments have demonstrated antigenic differences among JEV strains (1). Phylogenic studies have identified five JEV genotypes, four of which are presently recognized (5,55,62).…”
mentioning
confidence: 99%
“…It is estimated that JEV causes 35,000 to 50,000 cases of encephalitis, including 10,000 deaths and as many neurologic sequelae, each year (61). Although only one JEV serotype is known to exist, cross-neutralization experiments have demonstrated antigenic differences among JEV strains (1). Phylogenic studies have identified five JEV genotypes, four of which are presently recognized (5,55,62).…”
mentioning
confidence: 99%
“…1). JEV Nakayama, isolated in Japan in 1935, and SA14-14-2, an attenuated strain of SA-14 which was isolated in China in 1954, are both grouped in JEV genotype III based on phylogenetic analysis (1,2,12,22,38,39,51,52). Historically, isolates from Vietnam have also clustered into genotype III, with slightly higher homology to SA-14 than to Nakayama.…”
Section: Discussionmentioning
confidence: 99%
“…According to the continue public health impact of JE in Thailand, it has led to effort in childhood immunization and vaccine production in 1985. It was demonstrated by hemagglutination inhibition and neutralization assay that there are definitive antigenic differences among JEV Thai strain and between Thai strains and the standard subtypes, Nakayama and Beijing strains (Ali et al, 1995;Ali & Igarashi, 1997). Most of JEV isolated in Thailand are belonging to genotype I, while some belonging to genotype II, which strains Nakayama and Beijing are belonging to genotype III (Ali & Igarashi, 1997).…”
Section: Ecology Of Mosquito Vectormentioning
confidence: 99%
“…It was demonstrated by hemagglutination inhibition and neutralization assay that there are definitive antigenic differences among JEV Thai strain and between Thai strains and the standard subtypes, Nakayama and Beijing strains (Ali et al, 1995;Ali & Igarashi, 1997). Most of JEV isolated in Thailand are belonging to genotype I, while some belonging to genotype II, which strains Nakayama and Beijing are belonging to genotype III (Ali & Igarashi, 1997). The monovalent vaccine derived from JEV strain Nakayama or bivalent vaccine consisting of Nakayama and Beijing-1 strains provide 91% protective efficiency in either protocol in Thai children.…”
Section: Ecology Of Mosquito Vectormentioning
confidence: 99%